Unsteady boundary layer flow of a micropolar fluid near the forward stagnation point of a plane surface - Lok, Yian Yian; Phang, P.; Amin, Norsarahaida; Pop, Ioan (Elsevier Science Ltd., 2003)
The growth of the boundary-layer flow of a micropolar fluid started impulsively from rest near the forward stagnation point of a two-dimensional plane surface is studied theoretically. The transformed non-similar boundary-layer equations are solved numerically using a very efficient finite-difference method known as Keller-box method. This method may present well-behaved solutions for the transient (small time) solution and those of the steady-state flow (large time) solution. Numerical results are given for the reduced velocity and microrotation profiles, as well as for the skin friction coefficient when the material parameter K takes the value K=0 (Newtonian fluid), 0.5, 1, 1.5, 2, 2.5 and 3. Important features of these flow characteristics are shown on graphs and in tables